Novel Genomic Variants, Atypical Phenotypes and Evidence of a Digenic/Oligogenic Contribution to Disorders/Differences of Sex Development in a Large North African Cohort - Housna Zidoune; Housna Zidoune; Housna Zidoune; Asmahane Ladjouze; Djalila Chellat-Rezgoune; Djalila Chellat-Rezgoune; Asma Boukri; Scheher Aman Dib; Nassim Nouri; Meryem Tebibel; Karima Sifi; Noureddine Abadi; et al. (Frontiers in Genetics, 2022)
In a majority of individuals with disorders/differences of sex development (DSD) a genetic etiology is often elusive. However, new genes causing DSD are routinely reported and using the unbiased genomic approaches, such as whole exome sequencing (WES) should result in an increased diagnostic yield. Here, we performed WES on a large cohort of 125 individuals all of Algerian origin, who presented with a wide range of DSD phenotypes. The study excluded individuals with congenital adrenal hypoplasia (CAH) or chromosomal DSD. Parental consanguinity was reported in 36% of individuals. The genetic etiology was established in 49.6% (62/125) individuals of the total cohort, which includes 42.2% (35/83) of 46, XY non-syndromic DSD and 69.2% (27/39) of 46, XY syndromic DSD. No pathogenic variants were identified in the 46, XX DSD cases (0/3). Variants in the AR, HSD17B3, NR5A1 and SRD5A2 genes were the most common causes of DSD. Other variants were identified in genes associated with congenital hypogonadotropic hypogonadism (CHH), including the CHD7 and PROKR2. Previously unreported pathogenic/likely pathogenic variants (n = 30) involving 25 different genes were identified in 22.4% of the cohort. Remarkably 11.5% of the 46, XY DSD group carried variants classified as pathogenic/likely pathogenic variant in more than one gene known to cause DSD. The data indicates that variants in PLXNA3, a candidate CHH gene, is unlikely to be involved in CHH. The data also suggest that NR2F2 variants may cause 46, XY DSD.